TEACHERS NEED 15 TO EMBRACE CHANGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 November 2016 – In facing the challenges of 21 century education, teachers need to change together with the curriculum and pedagogy, in how they fulfil their tasks and to be resilient, futuristic and having "worldview", and possessing higherorder and solid "worldclass thinking".